2019
DOI: 10.1186/s42269-019-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some insecticide sequences on the injurious insect- pests of cotton plants

Abstract: Background: Cotton growers in Egypt have experienced severe economic loss from cotton bollworms, especially the pink bollworm, Pectinophora gossypiella (Saund.), and spiny bollworm, Earias insulana (Boisd.), so a field experiment was carried out to determine efficiency of eight insecticides in their seven sequence programs to evaluate the best solution for cotton bollworms problems, during two successive seasons. Results: The highest reduction percentages are effective sequences 7 and 5 (gave about 90% infesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The effect of recommended insecticides application against the spiny bollworm in this study was similar to that observed by Ansari and Kumar (1988), Saad et al . (2015) and Ismail (2019). The use of chlorpyrifos and lambda-cyhalothrin insecticides resulted in a high reduction in the E. insulana population.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of recommended insecticides application against the spiny bollworm in this study was similar to that observed by Ansari and Kumar (1988), Saad et al . (2015) and Ismail (2019). The use of chlorpyrifos and lambda-cyhalothrin insecticides resulted in a high reduction in the E. insulana population.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most damaging pest of cotton because it attacks the fruiting parts of the plant, [1]. The damage caused by bollworms as they feed on cotton buds, flowers and bolls results in 20-60% yield and quality loss, [2]. Three bollworm species cause main damage on cotton in India: the pink bollworm (Pectinophora gossypiella), the spotted bollworm (Earias vitella), and the American bollworm (Helicoverpa armigera), [3].…”
Section: Introductionmentioning
confidence: 99%